In Quest of Customary Tenure Security: Opportunities and Challenges of Land Use Planning in Tanzania - Method Julius Gwaleba (African Journal on Land Policy and Geospatial Sciences)
Mainstreaming land use planning for tenure security in rural areas is a key issue to both scholars, academia and policymakers as well as governments in most developing countries. The need for local land use decision-making for enhancing tenure security as well as trade-offs for deliberative decision-making are crucial to improving local community needs, interests and concerns. Deliberative decision-making seeks to respond to local needs, interests and concerns with legitimate and acceptable social, cultural and institutional practices. This paper focuses on examining the challenges and opportunities for land use planning on tenure security in rural Tanzania.  In-depth interviews, survey questionnaires, and documentary procedures were used to gather both primary and secondary data. The survey questionnaires were administered to 167 local landholders or users (respondents) at Kibegere, Kisawasawa and Igima villages in Kilombero District in South-Western Tanzania. A snowball sampling method for data collection from the respondents were employed. Also, a purposive sampling technique was used to collect data from 20 Key informants. The findings indicate less benefits for the local people over the existing rural land use planning process. The paper suggests the conceptual framework for supporting land use planning to strengthen actor’s interaction in the land use decision-making process towards enhanced tenure security outcomes within the context of participatory governance.